A Characterization of Multi-Wavelet Dual Frames in Sobolev Spaces. (3rd January 2020) - Zhang, Jianping; Li, Jiajia
Abstract : For the past few years, wavelet and multi-wavelet frames have attracted interest from researchers. In this paper, we address some of these problems in the setting of the Sobolev space, and characterize of multi-wavelet dual frames in these spaces by using a pair of equations.